Plan de gestión de residuos generados en el marco de la emergencia por el COVID 19 para sector peluquero en Barranquilla. - Vergara, Leonela; Arias, Carlos (Universidad Antonio Nariño, 2022)
This text deals with the organization and support that can be provided to the hairdressing sector, in this emergency that we are experiencing called COVID-19, within the regulations required by the national government and on its behalf the ministries of Health and Environment, establish a series of procedures for the activities that are developed by some unions, especially the hairdressing union, their standardization and control is associated with the effort that each representative places on it. Regarding the MANAGEMENT PLAN FOR WASTE GENERATED IN THE FRAMEWORK OF THE EMERGENCY BY COVID 19 FOR THE BARRANQUILLA HAIRDRESSING SECTOR, it is presented as a guide to those hairdressers that it is time and they are looking for a way to reactivate their economy; which should promote the initiatives and contributions that are provided in terms of knowledge so that this is possible. In any establishment of this nature or similar activity, we know that they are generators of hazardous waste; this can be a threat to the conditions in part of human health and the environment, if they are not given proper management from their source. In order to support the procedures of the hairdressers union and guarantee the protection of both nature and the human being, this research was designed all this under the current Colombian regulations on the management and handling of waste, which are mandatory for the micro-enterprises that generate them within their daily activities.